RNASE2 Mediates Age-Associated B Cell Expansion Through Monocyte Derived IL-10 in Patients With Systemic Lupus Erythematosus - Zhu, Yantong; Tang, Xiaojun; Xu, Yang; Wu, Si; Liu, Weilin; Geng, Linyu; Ma, Xiaolei; Tsao, Betty P.; Feng, Xuebing; Sun, Lingyun (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is characterized by the production of pathogenic autoantibodies. Ribonuclease A family member 2 (RNase2) is known to have antiviral activity and immunomodulatory function. Although RNASE2 level has been reported to be elevated in SLE patients based on mRNA microarray detection, its pathologic mechanism remains unclear. Here, we confirmed that RNASE2 was highly expressed in PBMCs from SLE patients and associated with the proportion of CD11c+T-bet+ B cells, a class of autoreactive B cells also known as age-associated B cells (ABCs). We showed that reduction of RNASE2 expression by small interfering RNA led to the decrease of ABCs in vitro, accompanied by total IgG and IL-10 reduction. In addition, we demonstrated that both RANSE2 and IL-10 in peripheral blood of lupus patients were mainly derived from monocytes. RNASE2 silencing in monocytes down-regulated IL-10 production and consequently reduced ABCs numbers in monocyte-B cell co-cultures, which could be restored by the addition of recombinant IL-10. Based on above findings, we concluded that RNASE2 might induce the production of ABCs via IL-10 secreted from monocytes, thus contributing to the pathogenesis of SLE.